A Successful Reconstruction Using a Frozen Autograft and a Pedicled Latissimus Dorsi Flap after a S12345B Shoulder Girdle Resection in a Patient with Osteosarcoma - Shimizu, Takamasa; Kido, Akira; Honoki, Kanya; Murata, Keiichi; Fujii, Hiromasa; Higuchi, Banryoku; Ishihara, Takashi; Takeshita, Yasufumi; Shima, Midori; Yajima, Hiroshi; Akahane, Manabu; Tanaka, Yasuhito (Journal of Reconstructive Microsurgery, 2012)
We present a case of high-grade osteosarcoma in the proximal humerus in an 8-year-old boy. Massive tumor expansion required a S12345B shoulder girdle resection according to the system of the Musculoskeletal Tumor Society. After wide resection, only a small portion of the distal humerus and none of the rotator cuff muscles would be spared. Because the humeral portion would be too short to support the stem and the soft tissue would be insufficient to cover prosthetic components, we designed a composite reconstruction using a frozen autograft and a pedicled muscle flap. At 2 years postoperatively, our patient exhibited good adaptation and had acquired fine dexterity of the upper limb. To our knowledge, this is the first report regarding a successful composite reconstruction after a S12345B shoulder girdle resection.
Keywords: frozen autograft; shoulder girdle resection; pedicled latissimus dorsi flap